DETERMINING THE FIRST PRIORITY OF THE FIRST ARSENAL LOCATION TO SUPPORT THE OPERATION OF THE INDONESIAN WAR SHIP IN SECURITY OF THE EASTERN INDONESIAN SEA REGION WITH AHP METHODS - I Nengah Putra A; Sukmo Hadi Nugroho; Okol Sri Suharyo; Cahyanto Cahyanto (JOURNAL ASRO, 2020)
Faced with conditions of life of the nation that continues to evolve into a multidimensional cover all areas of lifeof the nation, then certainly required the development and deployment of the total potential and power of thenation effectively. Therefore it is the power that was developed to deal with these threats must also have theability to multi-dimensional as well. Reality is always pushing to restructure the military concept of defense tobecome responsive and adaptable and tailored to the substance of the reforms in the defense. The mainproblem faced by Indonesia to develop a domestic defense industry is the inability of industry and educationsectors to absorb the fundamental aspects of the Revolution in Military Affairs (RMA). This inability does notallow Indonesia to experience significant breakthroughs in the application of RMA. So with reference to thecondition necessary to anticipate concrete steps in developing a systematic plan to build the defense industriesare able to anticipate the revolution in military affairs. Among priorities at once by selecting the appropriatestages of the development plan which includes the development of Main Equipment Weapon System, SpatialPlanning Area Defense, Civil Defense Development, and Spatial Structure of the Organization. And one of itsefforts is the creation of the ability of military logistics support system effective and efficient and responsive,which in this case is the development of Arsenal's arsenal of weapons and ammunition in terms of both qualityand quantity so that is always ready to face any condition of any contingency that would happen. Determiningpolicy location Arsenal first location contains more choices in environmental issues multiobjectiv andmulticriteria decision, then the model is proposed to be the appropriate methodology to accommodate thequalitative preference and priority-setting objectives / criteria for future development is to approach theAnalytical Hierarchy Process (AHP). Principle of the AHP method is to break breaking a complex situation andunstructured, into its component parts, arranging these variables in a section or an order of hierarchy, givingnumerical values to subjective considerations about the relative importance of each variable and analysisvarious considerations is to determine which variables have highest priority and act to influence the outcome ofthe situation. From the results of the solution by using AHP method showed that the first priority locationdetermination Arsenal 1 in the eastern region is a factor analysis of logistics operations to support operationscapabilities in integrated logistics support system that effectively and efficiently. And the locations selected forArsenal's first priority location is in the eastern region Lantamal Ambon. Keyword: Determining location - Approach of the Analytical Hierarchy Process (AHP)